Peran Pemberdayaan, Kepuasan Kerja, dan Komitmen Organisasional Terhadap Turnover Intention - Mustopa Mustopa; Lista Meria (Jurnal Syntax Transformation, 2021)
This study aims to determine the role of empowerment, job satisfaction, and organizational commitment on turnover intention in private employees who live in the Greater Jakarta area. The independent variables are empowerment, job satisfaction and organizational commitment, while the dependent variable is turnover intention. The population in this study are private employees who live in the Greater Jakarta area. The number of samples contained in this study were 150 respondents. The sampling technique contained in this study uses a non-probability sampling method with purposive sampling technique, the data instrument testing uses validity and reliability tests. The method used in this research is path analysis. Based on this research, it was found that empowerment has a positive and significant effect on organizational commitment. Empowerment has a negative and significant effect on turnover intention. Job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction has a negative and significant effect on turnover intention. Organizational commitment has no effect on turnover intention. Furthermore, organizational commitment does not mediate the relationship between empowerment and turnover intention. Then organizational commitment also does not mediate the relationship between job satisfaction and turnover intention